Therapy of bone infection with an antibiotic cement-coated intramedullary nail - preliminary results - Petráš, M; Ira, D; Bučka, L; Krtička, M; Kovařík, J (Rozhledy v chirurgii, 2024)
INTRODUCTION: Antibiotic cement-coated intramedullary nails (ACCINs) are an increasingly popular method in the treatment of FRI (fracture-related infections). FRI is a major challenge that poses a major problem for the treating physician and the health care system, both in terms of cost of therapy, time required, and the complexity of treatment with an uncertain outcome. The aim of our report is to evaluate the results of surgical management using ACCINs in patients with FRI who were treated during a 5-year period at our institution. METHODS: A retrospective evaluation of the results of surgical treatment using ACCINs in patients with FRI treated at the Department of Trauma Surgery, University Hospital Brno and Faculty of Medicine, Masaryk University in Brno in 2018-2022. Based on the exclusion criteria, 5 out of 18 patients were excluded from the study for the following reasons: a follow-up period less than 6 months, chronic immunosuppressive drug therapy, and any oncological or autoimmune disease. Bone infections in the femoral diaphysis, tibial diaphysis and infections in the ankle joint were among the inclusion criteria for the use of ACCINs. The study population consisted of 13 patients (3 women, 10 men); mean age was 48 years and median age was 44 years. Three patients had an infection after osteosynthesis in the femoral diaphysis, 7 patients had an infection in the tibial diaphysis and 3 had an infection in the ankle joint. RESULTS: In our cohort, bone healing without any clinical and laboratory signs of infection or stable arthrodesis was observed in 7 (54%) patients. In 3 cases (23%), healing proceeded without any signs of infection. In 3 patients (23%), further surgical treatment was required because of fracture nonhealing (n=1) and because of the combination of bone nonhealing and infection (n=2). The overall limb salvage rate was 100%. CONCLUSION: The use of ACCINs fulfills the three basic principles of bone infection therapy after thorough debridement: local action of antibiotics, filling of the dead space, and stabilization of the skeleton. ACCINs provide an effective method in the treatment of FRI of the diaphysis of long bones and septic arthritis of the ankle.
Keywords: senioři; Anti-Bacterial Agents; fraktury tibie; Retrospective Studies; fraktury femuru; Middle Aged; mužské pohlaví; Tibial Fractures; arthrodesis; Adult; FRI; ACCINs; Bone Nails; kostní hřeby; kostní cementy; ženské pohlaví; retrospektivní studie; Humans; Osteomyelitis; antibakteriální látky; lidé středního věku; Fracture Fixation, Intramedullary; Femoral Fractures; dospělí; Female; Aged; Bone Cements; intramedulární fixace fraktury; lidé; Male